Atypical aetiology of an abscess in the calcaneal region in an immunocompetent child: Salmonella spp. infection - Sosnowska-Sienkiewicz, Patrycja; Tomczak, Aleksandra; Kukfisz, Agata; Mańkowski, Przemysław (Pediatria Polska - Polish Journal of Paediatrics, 2022)
Non-typhoidal Salmonella spp. infections are causative factor of acute gastroenteritis, bacteraemia, subsequent focal infection and the asymptomatic carrier state. Non-typhoidal Salmonella spp. causes clinical symptoms, especially in neonates, infants, aged and immunocompromised patients. We report a case of an 8-year-old immunocompetent male patient admitted to our hospital with an abscess in the left calcaneal region. Swelling and pain in the foot made walking difficult. The patient did not experience injury or any infection, including gastroenteritis. The abscess was surgically drained and the intravenous antibiotic therapy was introduced. Salmonella spp. growth was yielded in the drainage material and the negative-pressure wound therapy with nanocrystalline silver layer was applied. A gradual improvement in the clinical condition was observed. The cause of the abscess remains unknown. It is often difficult to assess the cause of unusual lesions in a patient. Multidisciplinary care is necessary to enhance the effect of the therapy.